Transforming Health in Indonesia: A Pathway to Sustainable Development - Efendi, Ferry (Gaceta Médica de Caracas, 2023)
Good health is a crucial aspect of human well-being and an important indicator of a nation’s progress. To achieve sustainable development in the healthcare industry of Indonesia, it is essential to address the social determinants of health. Factors such as poverty, education, housing, and clean water availability play a significant role in determining the overall health of individuals and communities. By implementing policies that address these determinants, Indonesia can create an environment that promotes healthy living and improves health outcomes. In addition, encouraging community engagement and participation in healthcare decision-making processes can empower individuals and create a sense of ownership in their health, ultimately contributing to the success of Indonesia’s health transformation.